Comparison of Serum Levels of Vitamin D and Inflammatory Markers Between Women With Gestational Diabetes Mellitus and Healthy Pregnant Control - Fatemeh Haidari; Mohammad-Taha Jalali; Nahid Shahbazian; Mohammad-Hossein Haghighizadeh; Elham Azadegan (Tehran University of Medical Sciences, 2016)
Objective: Vitamin D appears to be involved in regulation of glycemic and inflammatory responses in gestational diabetes. The purpose of this study was to compare the serum levels of 25-hydroxyvitamin D (25(OH)D), inflammatory biomarkers and glycemic profile between gestational diabetes mellitus (GDM) and normal glucose tolerance (NGT) pregnant women. Materials and methods: In this cross-sectional study, fasting serum levels of 25(OH)D, insulin, glucose, HOMA-IR, hs-CRP and TNF-α were measured in 45 GDM and 45 NGT women at week 20-30 gestation whom referred to Reference Medical Laboratory of Ahvaz, Iran in 1394. Results: Serum 25(OH)D levels were significantly lower (p = 0.003 ) in the GDM group compared to the NGT group which remained even after controlling for confounders. Insulin and TNF-α levels were not statistically different between groups (p > 0.05). However, in unadjusted model, HOMA-IR and hs-CRP were significantly different between groups that disappeared in adjusted model. In the GDM group, there was a negative significant correlation between 25 (OH) D and fasting blood sugar (p = 0.009) and pre pregnancy BMI (p < 0.001). Levels of 25(OH)D were also negatively correlated with pre pregnancy BMI (p < 0.001) and hs-CRP levels (p = 0.003) in the NGT group. Conclusion: The lower level of vitamin D may be responsible for impairments of some glycemic and inflammatory markers in pregnant women. This is more important in overweight pregnant women. However, further studies with larger sample size are recommended in this regards.